Association between Vision Impairment and Physical Quality of Life Assessed Using National Surveillance Data. Issue 9 (September 2021) - VanNasdale, Dean A.; Jones-Jordan, Lisa A.; Hurley, Megan S.; Shelton, Erica R.; Robich, Matthew L.; Crews, John E.
Abstract : Supplemental digital content is available in the text. Abstract : SIGNIFICANCE: Physically unhealthy days assessments in national health surveillance datasets represent a useful metric for quantifying quality-of-life differences in those with and without vision impairment. Disproportionately poorer physical health in the visually impaired population provides further rationale for the inclusion of vision care in multidisciplinary approaches to chronic disease management. PURPOSE: This study aimed to assess the association between vision impairment and health-related quality of life using data from the Centers for Disease Control and Prevention's Behavioral Risk Factor Surveillance System. METHODS: Data from each of the 50 states were extracted from the 2017 Behavioral Risk Factor Surveillance System data set. Self-report of difficulty seeing was used to categorize visually impaired versus nonvisually impaired populations. Self-report number of physically unhealthy days in the previous 30 days was used to quantify quality of life. The number of unhealthy days was calculated for the visually impaired and nonvisually impaired cohorts for each state. The ratio of the number of physically unhealthy days in the visually impaired versus nonvisually impaired population was calculated for each state and for different age cohorts. RESULTS: Mean numbers of physically unhealthy days among persons with and without severe vision impairment across all states were 10.63 and 3.68 days, respectively, and demonstrated considerable geographic variability. Mean ratios of physically unhealthy healthy days in the visually impaired versus the nonvisually impaired population were 2.91 in the 18- to 39-year-old cohort, 2.87 in the 40- to 64-year-old cohort, and 2.16 in the ≥65-year-old cohort. CONCLUSIONS: National surveillance data demonstrate a greater number of physically unhealthy days in the visually impaired population, indicating a need to improve our understanding of causes that lead to reduced physical health among those with vision impairment. Additional research is needed to better understand how individuals perceive vision as part of their overall health.